Feeding ecology informs parasite epidemiology: prey selection modulates encounter rate with Echinococcus multilocularis in urban coyotes. - Stefano Liccioli; Carly Bialowas; Kathreen E Ruckstuhl; Alessandro Massolo (PLoS ONE, 2015)
We investigated the role of urban coyote feeding ecology in the transmission of Echinococcus multilocularis, the causative agent of Alveolar Echinococcosis in humans. As coyotes can play a main role in the maintenance of this zoonotic parasite within North American urban settings, such study can ultimately aid disease risk management. Between June 2012 and June 2013, we collected 251 coyote feces and conducted trapping of small mammals (n = 971) in five parks in the city of Calgary, Alberta, Canada. We investigated E. multilocularis epidemiology by assessing seasonal variations of coyote diet and the selective consumption of different rodent intermediate host species. Furthermore, accounting for small mammal digestibility and coyote defecation rates we estimated the number of small mammal preys ingested by coyote and consequently, coyote encounter rates with the parasite. Dominant food items included small mammals, fruit and vegetation, although hare and deer were seasonally relevant. The lowest frequency of occurrence per scat of small mammals was recorded in winter (39.4%), when consumption of deer was highest (36.4%). However, highest encounter rates (number of infected hosts predated/season) with E. multilocularis (95% CI: 1.0-22.4), combined with the lack of predation on non-competent small mammal species, suggest that winter is the critical season for transmission and control of this parasite. Within the small mammal assemblage, voles (Microtus pennsylvanicus and Myodes gapperi) were the selected preys of urban coyotes and likely played a key role for the maintenance of the urban sylvatic life-cycle of E. multilocularis in Calgary.